Stearoyl CoA desaturase and fatty acid synthase gene polymorphisms and milk fatty acid composition in Chilean Black Friesian cows - Inostroza, Karla B; Scheuermann, Erick S; Sepúlveda, Néstor A (Revista Colombiana de Ciencias Pecuarias, 2013)
Summary Background: in recent years, market attention has increasingly focused on improving the quality of dairy products. Therefore, animal selection for healthier milk fatty acid composition are therefore of interest. Objective: the aim of this study was to identify whether two polymorphisms (c.878T>C in the SCD gene and g.17924A>G in the FASN gene) are related with the fatty acid composition of milk. Methods: individual milk samples were collected from 50 Chilean Black Friesian cows. Fatty acids (FA) from each milk sample were extracted, analyzed, and quantified (mg FA/g of milk) by gas chromatography. The genotype of each sample was also determined using PCR-RFLP (Polymerase Chain Reaction - Restriction Fragment Length Polymorphism). Results: milk from cows with a c.878CC genotype in the SCD gene exhibited a greater content of C14:1, C17:1, C18:1n9t, C18:1n9c, and total monounsaturated fatty acids (MUFA), as well as a higher 14:1/14 ratio than other SCD genotypes. In addition, considering the importance of the predominant isomer of conjugated linoleic acid for human diet, we identified a higher content of cis-9, trans-11 conjugated linoleic acid in milk samples from animals that had the c.878CC genotype. For the FASN gene, cows with the g.17924GG genotype presented high contents of C14:0, C16:0, C18:0, C18:1n9t, C18:1n9c, and MUFA. Conclusion: therefore, these polymorphisms could be useful genetic markers for studying the fatty acid composition of dairy milk. Key words: conjugated linoleic acid, monounsaturated, SNP. Resumen Antecedentes: en los últimos años, la atención del mercado se ha centrado cada vez más en mejorar la calidad los productos lácteos. Por lo tanto, la selección de animales con una composición de ácidos grasos de leche más saludable es de interés. Objetivo: el principal objetivo de este estudio fue identificar dos polimorfismos (c.878T>C en el gen SCD y g.17924A>G en el gen FASN) y su relación con la composición de ácidos grasos de leche. Métodos: muestras individuales de leche fueron recolectadas de 50 vacas Frison Negro Chileno. Los ácidos grasos (FA) de cada muestra de leche fueron extraídos, analizados y cuantificados (mg FA/g leche) por cromatografía de gases. El genotipo de cada muestra se determinó mediante la técnica PCR-RFLP (reacción en cadena de la polimerasa - polimorfismo de longitud de fragmentos de restricción). Resultados: los animales con el genotipo c.878CC en el gen SCD presentaron un mayor contenido de C14:1, C17:1, C18:1n9t, C18:1n9c y total de ácidos grasos monoinsaturados (MUFA), así como elevados índices de 14:1/14 que otros genotipos SCD. Además, debido a la importancia en la dieta humana del isómero predominante de ácido linoleico conjugado (CLA), hemos identificado un mayor contenido de cis-9, trans-11 CLA en muestras de leche de animales que poseen el genotipo c.878CC. Para el gen FASN, vacas con el genotipo g.17924GG presentaron un mayor contenido de C14:0, C16:0, C18:0, C18:1n9t, C18:1n9c y contenido total de ácidos grasos monoinsaturados (MUFA). Conclusión: por lo tanto, estos polimorfismos podrían servir como marcadores genéticos para el estudio de la composición de ácidos grasos en la leche de vaca. Palabras clave: ácido linoleico conjugado, monoinsaturados, SNP. Resumo Antecedentes: nos últimos anos, o mercado fornecedor de laticínios tem-se voltado ao melhoramento da qualidade dos seus produtos. Por conseguinte, é de interesse a seleção de animais que apresentem uma composição de ácidos graxos mais saudáveis no seu leite. Objetivo: o objetivo principal deste estudo foi identificar dois polimorfismos (c.878T>C no gene SCD e g.17924A>G no gene FASN) e sua associação com a composição de ácidos graxos do leite. Métodos: as amostras de leite foram coletadas de 50 vacas Frison Preto Chileno. Os ácidos graxos (FA) de cada amostra de leite foram extraídos, analisados e quantificados (mg FA/g leite) por cromatografia gasosa. O genótipo de cada amostra foi determinado pela reação de PCR-RFLP (Reação em cadeia de polimerase - polimorfismo de comprimento dos fragmentos de restrição). Resultados: os animais com o genótipo c.878CC no gene SCD têm um teor mais elevado de C14:1, C17:1, C18:1n9t, C18:1n9c e do total de ácidos graxos monoinsaturados (AGM), além de níveis mais elevados de 14:1/14 que outros genótipos SCD. Além disto, devido à importância na dieta humana do isômero predominante do ácido linoléico conjugado (CLA), identificou-se um maior teor de cis-9, trans-11 CLA nas amostras de leite de animais que tinham o genótipo c.878CC. Para o gene FASN, as vacas com o genótipo g.17924GG tinham um teor mais elevado de C14:0, C16:0, C18:0, C18:1n9t, C18:1n9c e AGM. Conclusão: estes polimorfismos poderiam ser usados como marcadores genéticos para o estudo da composição de ácidos graxos do leite de vaca. Palavras chave: ácido linoléico conjugado, monoinsaturados, SNP.